PREVALENSI MYIASIS PADA KERBAU DI PULAU MOA, KABUPATEN MALUKU BARAT DAYA - Jemmy Max Lakuteru; Astri Dwyanti Tagueha; Isak Siwa; Demianus Ferdinand Souhoka; Feronica Parera (BUANA SAINS, 2022)
The study aimed to determine the prevalence of myiasis in buffalo at Moa island. Data collection was carried out from April to December 2020 using a survey method in 3 villages selected by stratified random sampling. Samples of  98 buffaloes were selected using the detect disease method and taken from four villages. The results showed that the prevalence rate of myiasis in buffalo was 7.14% with details of the prevalence at the village level, namely Tounwawan 9%, Nyama 6%, and Klis 4%. Myiasis was founded in adult buffalo and it was caused by the Chrysomya bezziana. The number of flies per site infestation was 11-23 heads with a duration of 3.09-4.17minutes. The favorable site for oviposition were the neck, back, thighs, and vulva. The predisposing factors that caused the injury were headers, bird pecks, and bush punctures. Maggots had burrowed deep inside causing necrotic cavities, malodorous, and reddish-brown fluid.